(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the implementation of the Common European Framework of Reference for Languages (CEFR) in the context of one higher education institution in Uzbekistan, teachers’ views on the CEFR, and challenges in applying it. In order to study the impact of the CEFR and the challenges caused by its application, a survey among 32 English language teachers working in different higher education institutions was conducted. The results of the research revealed that the implementation of the CEFR and its role in reforming the system of learning and teaching foreign languages in Uzbekistan were significant. The study also revealed that although the system of learning and teaching foreign languages benefited from adopting the CEFR in developing national standards and curricula, foreign language teachers still need assistance and support in mastering the application of the CEFR in their teaching practices.